2010
DOI: 10.4269/ajtmh.2010.09-0699
|View full text |Cite
|
Sign up to set email alerts
|

Rabies Exposure Risk among Foreign Backpackers in Southeast Asia

Abstract: Abstract. Rabies remains a problem in Southeast Asia where large numbers of backpackers visit each year. During May-June 2008, a survey study was conducted of foreign backpackers in Bangkok, Thailand to assess their risk of rabies exposure . Eight hundred seventy (870) questionnaires were collected and analyzed. The median age of the backpackers was 25.5 years. Most of them were European (68.4%), followed by North American (13.2%). Although 80.7% had sought health information before traveling, only 55.6% had r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 14 publications
4
29
3
Order By: Relevance
“…Majority (97.1%) of them said that dog harbours rabies organism, which was consistent with the findings of Piyaphenee et al 6 , Mitabug et al 7 , Singh et al 8 Almost 9 in 10 of the participants told that bite of the dog could spread the disease, which was consistent with Piyaphenee et al 6 , Mitabug et al 7 , Prakash et al 9 Eighty seven percent respondents told that rabies was a fatal disease, which was concurrent with the finding where 84.9% of the respondents said that rabies could lead to death. 6 Two-third of the respondents said that head was the most dangerous site of bite, which was in contrast with Prakash et al 9 In our study 49.4% of respondents said that rabies could be prevented by vaccination which was in contrast with one study. 6 which found almost 90% of the respondents had the idea that vaccination could prevent rabies, but similar with the finding of Prakash et al 9 In our study, nearly 1% of the respondents said that they should wash the bite wound with either water or water and soap which is in contrast with the study findings where more than 50% of them were aware of it.…”
Section: Discussionsupporting
confidence: 89%
“…Majority (97.1%) of them said that dog harbours rabies organism, which was consistent with the findings of Piyaphenee et al 6 , Mitabug et al 7 , Singh et al 8 Almost 9 in 10 of the participants told that bite of the dog could spread the disease, which was consistent with Piyaphenee et al 6 , Mitabug et al 7 , Prakash et al 9 Eighty seven percent respondents told that rabies was a fatal disease, which was concurrent with the finding where 84.9% of the respondents said that rabies could lead to death. 6 Two-third of the respondents said that head was the most dangerous site of bite, which was in contrast with Prakash et al 9 In our study 49.4% of respondents said that rabies could be prevented by vaccination which was in contrast with one study. 6 which found almost 90% of the respondents had the idea that vaccination could prevent rabies, but similar with the finding of Prakash et al 9 In our study, nearly 1% of the respondents said that they should wash the bite wound with either water or water and soap which is in contrast with the study findings where more than 50% of them were aware of it.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is similar to those of previous studies that found that most travelers are not vaccinated for rabies before travel (Altmann et al 2009, Gautret et al 2008, Piyaphanee et al 2010. Specifically, 60% of GTEN travelers visiting a single strong- a Travelers could choose more than one purpose for travel; therefore, the total purposes of travel exceed the number of vaccinated travelers (n = 406) and unvaccinated travelers (n = 12,603).…”
Section: Discussionsupporting
confidence: 80%
“…Other studies have found that travelers refused vaccination because of high cost, low perception of benefit, concern for an adverse reaction, and belief that vaccination was not necessary (Altmann et al 2009, Piyaphanee et al 2010. In fact, the average wholesale price of an individual rabies vaccine dose for pre-exposure vaccination can range from $194 to $240 (Anonymous 2008).…”
Section: Dolan Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…These studies demonstrated a high level of people's awareness regarding rabies. A few other studies have also reported about knowledge and perception of rabies risk among travelers travelling in rabies-endemic countries (Altmann et al, 2009;Piyaphanee et al, 2010). However, these studies have also found that people apply chilli and turmeric powder, lime, kerosene oil, herbal paste or salt on the dog bite wound, or perform folk remedies at home rather than seeking conventional treatment from health facilities (Agarvval and Rabies is endemic in south Bhutan (an area that borders India) and results in sporadic human deaths (approximately 0.28 deaths per100000 population per year) following rabid dog bites (Tenzin.…”
Section: Introductionmentioning
confidence: 99%